Job Satisfaction of Bank Employees In Delhi A Comparative Study of Private & Public Sector Bank (Hdfc Bank & Uco Bank): Examining Job Satisfaction of Bank Employees in Delhi: A Comparative Study of Private and Public Sector Banks (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The success of an organization depends not merely on itstechnical efficiency, updated machinery, good plant layout and dynamicorganization etc; but also depends upon its human recourses. A satisfied, happyand hardworking employee is the biggest asset of any organization, includingbanks. Workforce of any bank is responsible to a large extent for itsproductivity and profitability. So, for the success of banking, it is veryimportant to manage human resource effectively and to find whether itsemployees are satisfied or not. If finance is considered the lifebloodof the business, human resource can be aptly called the soul of business.